A Comparison of the Biomechanical Performance of 3 Negative Pressure Wound Therapy Foams. Issue 1 (1st January 2022) - Gibson, Daniel J.
Abstract : PURPOSE: The purpose of this study was to compare 3 foam dressings to (1) determine the biomechanical performance of existing negative pressure wound therapy (NPWT) foams and (2) to determine if a test foam is possibly suitable as an antimicrobial "white" foam alternative for use in NPWT. DESIGN: A comparison of mechanical performance of 3 foams used for vacuum-assisted NPWT. SUBJECTS AND SETTING: Preclinical laboratory study using an in vitro model. METHODS: The performance of a "white" foam (polyvinyl alcohol [PVA]), an antimicrobial "black" foam (polyurethane [PU]), and an antimicrobial white foam alternative (test PVA) were tested and compared using 3 mechanically relevant criteria. First, the fluid removal rate was measured for 72 hours. Next, the pressure input was compared to the pressure directly beneath the center of the foam. Finally, the spread of negative pressure beneath the foam was measured and compared. RESULTS: Significant differences were found in fluid removal rates; specifically, the PU foam removed fluids faster than the PVA and test PVA foams, and the currently available PVA foams performed similarly. Both the PU and test PVA foams were able to transmit the negative pressure through the center of the dressing, while the typical PVA foam began failing at 140 mm Hg, with 50% of the samples failing at 200 mm Hg. All PU replicate foams evenly distributed the pressure, while 47% to 60% of the test PVA foams and 7% of the typical PVA foams distributed pressures evenly. CONCLUSIONS: Study findings suggest that the test PVA foam does not mechanically interfere with NPWT and performs equivalently to currently used foams. These results suggest that the test PVA may be modified and incorporated into a vacuum-assisted NPWT device. In addition, the methods employed in these experiments provide a reproducible means to compare biomechanical compatibility of various NPWT foams, dressings, and subdrape devices.